The contributions of university editions to research in Peru - Antonioli Delucchi, Dante (2005)
Two years ago, there was a turning point in the volumes produced and marketed by the Peruvian publishing sector. After several years of generalized crisis and uncontrollable growth in piracy, the results began to reverse and a substantial improvement was observed in editorial production, in titles produced, in export-import volumes, and in the mix of products . Apparently, the benefits of the harshly criticized Law for the Democratization of Books and the Promotion of Reading had begun to be perceived among the companies in the sector.